JEZUS CHRYSTUS, NASZA NADZIEJA - Andrzej Dziuba (Studia Theologica Varsaviensia)
Questions about man, his freedom and liberation, are very important for human existence. Jesus Christ and His paschal mystery are the roots of Christian hope. Jesus is hope’s bearer, however He requires our trust. Jesus Christ fulfills in Himself all the Messianic promises, especially the one of salvific newness of life in the New Covenant, also called the new humanity. The central sign of this newness is the coming of God’s Kingdom. The universality of the Resurrection’s gift brings us hope that all human beings might experience new life. The salvific gift refers to the renewal of the world in the renewal of all men. And yet, the voice of the culture of death—which is the negation of man, his dignity and his hope—is loudly heard in today’s world. The culture of life, on the other hand, brings real hope, especially when it is marked by respect for life. The Christian attitude is one of thanking and praising the Lord in the power of the Holy Spirit. Christ is the hope of the people, of the world, and, therefore, of the new evangelization.